Monocyte adhesion to and transmigration through endothelium following cardiopulmonary bypass shearing is mediated by IL-8 signaling - Zhou, Hao; Scatena, Marta; Tu, Lan N.; Giachelli, Cecilia M.; Nigam, Vishal (Frontiers in Cardiovascular Medicine, 2024)
IntroductionThe use of cardiopulmonary bypass (CPB) can induce sterile systemic inflammation that contributes to morbidity and mortality, especially in children. Patients have been found to have increased expression of cytokines and transmigration of leukocytes during and after CPB. Previous work has demonstrated that the supraphysiologic shear stresses existing during CPB are sufficient to induce proinflammatory behavior in non-adherent monocytes. The interactions between shear stimulated monocytes and vascular endothelial cells have not been well studied and have important translational implications. With these studies, we tested the hypothesis that non-physiological shear stress experienced by monocytes during CPB affects the integrity and function of the endothelial monolayer.MethodsWe have used an in vitro CPB model to study the interaction between THP-1 monocyte-like cells and human neonatal dermal microvascular endothelial cells (HNDMVECs). THP-1 cells were sheared in polyvinyl chloride (PVC) tubing at 2.1 Pa, twice of the physiological shear stress, for 2 h. ELISA, adhesion and transmigration assays, qPCR, and RNA silencing were used to assess the interactions between THP-1 cells and HNDMVECs were characterized after co-culture.ResultsWe found that sheared THP-1 cells adhered to and transmigrated through the HNDMVEC monolayer more readily than static THP-1 controls. Sheared THP-1 cells disrupted the VE-cadherin and led to the reorganization of cytoskeletal F-actin of HNDMVECs. A higher level of IL-8 was detected in the sheared THP-1 and HNDMVEC co-culture medium compared to the static THP-1 and HNDMVEC medium. Further, treating HNDMVECs with IL-8 resulted in increased adherence of non-sheared THP-1 cells, and upregulation in HNDMVECs of vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1). Finally, inhibition of HNDMVECs CXCR2/IL-8 receptor with Reparixin and of IL-8 expression with siRNA blocked sheared THP-1 cell adhesion to the endothelial monolayer.ConclusionsThese results suggest that CPB-like sheared monocytes promote IL-8 production followed by increased endothelium permeability, and monocyte adhesion and transmigration. This study revealed a novel mechanism of post-CPB inflammation and will contribute to the development of targeted therapeutics to prevent and repair the damage to neonatal patients.